Development of TNB distribution network risk based asset replacement policy and guideline for medium voltage primary equipment - S. Balasubramaniam, Yogendra; Talib, Mohd Aizam; Raj, Avinash; Dzaki, Mohd; Bala Sundaram, Mithila Seva; Mohd Yousof, Mohd Fairouz (Penerbit UTHM, 2020)
Asset Management (AM) is the systematic and coordinated activity of an organization to realize value from assets, through which an organization optimally and sustainably manages its assets and asset systems, their associated performance, risk and expenditures over their life cycle for the purpose of achieving its organizational strategic plan. An effective AM System enables TNB Distribution to establish and verify a holistic view of asset management throughout an asset’s whole life. It facilitates an optimal mixture of capital, operations, maintenance, resourcing, risks, performance and sustainability within a framework of good governance.